Outcome Of Prostatic Abscess By Transurethral Resection In Diabetic Patients (Bangladesh Journal of Urology, 2020)
Purpose: Prostatic abscess is an uncommon urologic disease but has a high mortality rate if not treated properly. Furthermore, diagnosis and proper treatment of prostatic abscess remain as a challenge for physicians. Transurethral resection of prostate in prostatic abscess is found very effective considering its rapid recovery. We compared data on transurethral resection of prostate (TURP), and transurethral incision of the abscess cavity (TUI) in 117 cases over a six and half year period.The details of surgical resection and all the followup visits were recorded and analyzed.Results: With a mean age of 61.53 ± 8.58 years, all diabetic patients had multifocal abscess cavities. Seventy six men underwent classical TURP similar to the technique used for benign prostatic enlargement(group 1), other 41 men underwent modified transurethral incision of the abscess cavity (TUI) (group 2). The abscess cavities resolved completely, and no patient required a second intervention. One patient in group 1 and 6 in group2 had postoperative fever requiring parenteral antibiotics (P = 0.716), 23 patients in group 1 had transient urinary incontinence,whereas none of the patients in group 2 had this complication (P = 0.055). 24 and 2 men in group 1 and 2 reported retrograde ejaculation respectively (P = 0.740). For the alleviation of symptoms and to get the urine culture negative post-operative antibiotic treatment was needed to be continued in group 1 for 7 days and in group 2 for more than 14 days.Conclusion: The modified resection technique of abscess cavity and formal TURPin the management of prostatic abscess give comparable outcome, but in diabetic patients as the abscess is multifocal transurethral resection ensures better drainage and faster postoperative recovery.Bangladesh Journal of Urology, Vol. 20, No. 1, January 2017 p.8-12